“Crisis, Chaos, Violence – Is that Really what We Want?” A Stalled Democratization in Jordan - Malantowicz, Artur (The Copernicus Journal of Political Studies, 2018)
Amidst the regional turmoil in the Middle East, the Hashemite Kingdom of Jordan prevails its relative stability despite undergoing only limited democratic reforms. The article aims to present and analyze the Jordanian regime’s reaction to the Arab Spring in light of the international historical sociology, which depicts multidimensional and interlinked relations between the state, socjety and international environment, all immersed in historical context. The analysis finds that Jordan is a case proving that some nations praise stability over rushed political reform and, what is a key to understand the phenomenon, this is the view shared not only among the ruling elite but also by a vast part of the society. The somewhat stalled democratisation works in favour of the autocratic regime of King Abdullah II who retains power, of the Jordanian society, which does not have to fear internal disorder, and of the international community for whom Jordan is a long-standing and reliable partner. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14763